FEATURES IN THE RELATIONSHIP OF CYTOCHEMICAL, METABOLIC ACTIVITY OF LEUKOCYTES IN THE TREATMENT OF EARLY CHILDREN WITH OBSTRUCTIVE BRONCHITIS (World Bulletin of Public Health, 2023)
The article provides data on the definition and rationale for the inclusion of immunomodulin in a complex of therapeutic measures for sick young children with acute obstructive bronchitis and bronchiolitis . The effectiveness of the drug immunomodulin was assessed by the period (days) of disappearance of symptoms of respiratory failure and intoxication in children during the period of treatment.
Keywords: Obstructive syndrome; bronchitis; bronchiolitis; children